The Role of the Indonesian Navy in Human Resource Planning to Support the Free Nutritious Meal Program in Strengthening National Defense - Topani, Ilham; Budiman, Arief; Setiawan, Agung (AGUSPATI Research Institute, 2025)
Healthy and qualified human resources (HR) are key to supporting national defense, as they contribute optimally to the defense sector. The free nutritious meal program launched by the Indonesian government aligns with the 2025 global nutrition targets, aiming to improve the nutrition of schoolchildren and pregnant women, as well as address issues such as stunting, anemia, and wasting. While this program has significant potential to enhance national resilience, challenges such as a lack of trained personnel and ineffective coordination need to be addressed. This study aims to analyze the role of the Indonesian Navy (TNI AL) in HR planning to ensure the program's effectiveness and create healthy and productive human resources. The research method used is qualitative. The findings show that there are three main challenges in the implementation of the free nutritious meal program in Indonesia: the shortage of trained personnel, food distribution gaps in remote areas, and ineffective inter-agency coordination. The TNI AL can help address these issues by improving HR planning, providing competency-based training, and utilizing technology for more efficient distribution. Furthermore, enhancing inter-agency coordination through cross-sectoral teams and an integrated information system can strengthen the program's effectiveness and ensure equitable nutrition across Indonesia.